Ragone Relations for Thermal Energy Storage Technologies - Yazawa, Kazuaki; Shamberger, Patrick J.; Fisher, Timothy S. (Frontiers in Mechanical Engineering, 2019)
The Ragone relation is a facile approach to assess and compare electro-chemical battery performance in terms of two critical performance parameters: power density and energy density. This power and energy nexus is equally relevant for thermal energy storage materials for thermal management applications that require a balance between energy storage capacity and on-demand cooling or heating rates. Here, thermal energy storage is evaluated for sensible heating and for phase-change materials (PCMs). We propose an analytic expression using a lumped mass model for thermal storage through an analogy with heat diffusion that allows for intuitive mapping of materials and components in power-energy space. In addition, a previously proposed figure-of-merit, ηq, describing the intrinsic capability of PCMs to rapidly absorb or discharge heat is placed in the context of the thermal Ragone (power-energy) relation. This figure of merit serves as a proxy for the cooling power of PCMs and single-phase materials to store thermal energy. Thus, ηq plotted against energy density can serve graphically to illustrate performance tradeoffs between different thermal storage materials, as well as composites composed of different materials.